2021
DOI: 10.3390/ijms222212518
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regeneration of a 3D-Printed Alloplastic and Particulate Xenogenic Graft with rhBMP-2

Abstract: This study aimed to evaluate the bone regeneration capacity of a customized alloplastic material and xenograft with recombinant human bone morphogenetic protein-2 (rhBMP-2). We prepared hydroxyapatite (HA)/tricalcium phosphate (TCP) pure ceramic bone blocks made using a 3D printing system and added rhBMP-2 to both materials. In eight beagle dogs, a total of 32 defects were created on the lower jaws. The defective sites of the negative control group were left untreated (N group; 8 defects), and those in the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In seven articles, the matrix of the experimental group contained bone morphogenetic protein-2 (BMP-2) [ 28 , 42 , 45 , 49 , 88 , 89 ]. Bone regeneration was superior in all experimental groups, with the exception of three articles [ 90 , 91 , 92 ], which found similar values between the control and experimental group. Regarding secondary outcomes, Van Hede et al [ 73 ] analyzed matrix geometry, and found that the gyroid geometry results in better outcomes when compared to the orthogonal one.…”
Section: Resultsmentioning
confidence: 83%
“…In seven articles, the matrix of the experimental group contained bone morphogenetic protein-2 (BMP-2) [ 28 , 42 , 45 , 49 , 88 , 89 ]. Bone regeneration was superior in all experimental groups, with the exception of three articles [ 90 , 91 , 92 ], which found similar values between the control and experimental group. Regarding secondary outcomes, Van Hede et al [ 73 ] analyzed matrix geometry, and found that the gyroid geometry results in better outcomes when compared to the orthogonal one.…”
Section: Resultsmentioning
confidence: 83%
“…Previous studies have reported that scaffolds fabricated with varying proportions of HA and β-TCP can effectively stimulate stem cell differentiation into osteogenic lineages and facilitate fresh osseous tissue generation. These scaffolds align with the natural processes of bone regeneration and reconstruction. , Herein, we used ALP and alizarin red staining to show that SHSS can help enhance ALP expression and calcium nodule formation in BMSCs, indicating that it can help in the early and late stages of bone cell differentiation. Additionally, we observed a gradual increase in the mRNA expression levels of the Col-1 , OCN , and OPN genes at various time points (3, 7, and 10 days) during the osteogenic differentiation of BMSCs.…”
Section: Discussionmentioning
confidence: 91%
“…In a recent study, a 3D-printed calcium phosphate scaffold was fabricated according to the geometry of artificial alveolar clefts in rats and showed promising scaffolding and osteoconductive properties ( Korn et al, 2020 ). A 3D-printed custom hydroxyapatite/TCP graft supplied with rhBMP2 also achieved bone regeneration to the same level of rhBMP2-coupled deproteinized bovine bone material (Bio-Oss ® ) ( Ryu et al, 2021 ). Although the exact mechanism of how 3D-printed scaffolds benefit orthodontic tooth movement remains unmapped, evidence suggests that grafting with 3D-printed scaffolds may offer enhanced orthodontic outcomes.…”
Section: Materials With 3d Printed Scaffoldsmentioning
confidence: 99%